COMMUNICATION NETWORK AMONG THE VARIOUS TRIBAL COMMUNITIES OF THE NILGIRI HILLS - Sivashanmugam, M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Nilgiri Hills are home to several tribal communities, each with their distinct culture and language. Effective communication is crucial for their social, economic, and cultural well-being. However, the region's remote and rugged terrain, limited infrastructure, and socio-economic constraints pose significant challenges to communication. Language plays a vital role in shaping their identity, culture, and daily life. However, the region's linguistic diversity faces challenges due to urbanization, migration, and globalization. This study investigates the communication networks and challenges faced by tribal communities in the Nilgiri Hills. We conducted interviews and surveys among three tribal groups, examining their access to and utilization of communication channels. Our findings highlight limited access to modern communication technologies, reliance on traditional modes, and significant barriers to effective communication. We discuss the implications for social inclusion, economic development, and cultural preservation, and propose strategies for improving communication infrastructure and addressing the unique needs of these communities. This study delves into the linguistic behavior and problems faced by tribal communities in the Nilgiris Hills, a region renowned for its linguistic diversity. Through a mixed-methods approach, we investigated language use, language attitudes, and language challenges among three tribal groups: Toda, Kota, and Irula. Our findings reveal a complex linguistic landscape, with language shift, language loss, and language maintenance efforts. We discuss the implications for language preservation, education, and social inclusion, and propose strategies for supporting linguistic diversity and addressing linguistic problems in these communities. Methodology: We conducted interviews with 100 participants from three tribal groups (Toda, Kota, and Irula) and surveyed 50 households. We examined access to and usage of communication channels, including mobile phones, internet, radio, and traditional modes. We employed a mixed-methods approach, combining surveys, interviews, and focus groups with 300 participants from the three tribal groups. We examined language use, language attitudes, language proficiency, and language challenges. Conclusion: Enhancing communication networks and addressing the unique challenges faced by tribal communities in the Nilgiri Hills is crucial for their social inclusion, economic development, and cultural preservation. By bridging the communication gap, we can empower these communities to access information, resources, and opportunities, ultimately improving their overall well-being. The linguistic diversity of the Nilgiri Hills' tribal communities is a valuable asset, but faces significant challenges. By understanding the linguistic behavior and problems, we can develop targeted strategies to support language preservation, education, and social inclusion. Empowering these communities to maintain and promote their languages will enrich India's linguistic heritage and foster a more inclusive society. In total this study examines multilingualism among tribal communities in the Nilgiri Hills, a region known for its linguistic diversity. Through a mixed-methods approach, we investigated language use, language proficiency, and language attitudes among three tribal groups: Toda, Kota, and Irula. Our findings reveal a complex multilingual landscape, with tribal languages, dominant languages (Tamil, Malayalam), and bilingualism/multilingualism. We discuss the implications for language preservation, education, and social inclusion, and propose strategies for supporting multilingualism and linguistic diversity in these communities.